The Prevalence and Characteristics of Depression in Work-related Musculoskeletal Disease - Kwak, Jehwan (Korean Academy of Rehabilitation Medicine, 2012)
OBJECTIVE: To reveal the relationship between depression and WMSD. METHOD: Five physiatrists participated in the workplace musculoskeletal survey and diagnosed 724 office workers with WMSD by performing detailed history taking and physical examination. All subjects were asked to answer the Korean version of the Beck depressive inventory (K-BDI), and to express their pain according to the visual analogue scale (VAS) score. We categorized the subjects into 4 groups, myofascial pain syndrome (MPS), herniated intervertebral disk (HIVD), tenosynovitis, and others, and investigated the prevalence of depression in desk workers and relationship between WMSD and depression, and we compared pain intensity between the depression and non-depression groups. Correlation analysis was carried out between K-BDI and VAS scores in each group. RESULTS: The mean K-BDI score were 8.7±6.68. The prevalence of depression was higher in females than in male, and there was no relationship between age and depression. There was a significant connection between HIVD and depression (p<0.05). However, the other groups did not have significant connection to depression. The VAS score (5.02) of the depression group was significantly higher than that (4.10) of the non-depression group. In addition, there was a significant difference of VAS scores between the depression group and non-depression group in each disease group. CONCLUSION: The mean VAS score of the depression group in WMSD was significantly higher than in the non-depression group. The correlation between BDI and VAS scores in the subjects was present, and the highest was in the HIVD group.